Pengaruh Kondisi Eksisting dan Kemiringan Lereng Terhadap Stabilitas Lereng Menggunakan Metode Linear Discriminant Analysis - Fajar Yudha Pratama; I Nengah Sinarta; Ni Made Widya Pratiwi (Jurnal Konstruksi, 2024)
Landslides on slopes are the second most frequent natural disaster after floods which cause many losses if they occur. Therefore, it is necessary to predict slope failure to prevent it. One of them is the slope in Trunyan village, Bangli sub-district, Bali. In predicting slope vulnerability in this area, the Linear Discriminant Analysis method was used from 40 slope points using 2 variables, which is the existing condition of the slope and the slope of the slope, only 40.7 percent of the total variables that influence the slope with the results of the analysis there were 28 slope points from the 40 slope points. There are indications of landslides or 70 percent, the relatively small Wilks Lambda is 0.593 and the significance is less than 0.01, making the results of this research suitable for use. This analysis shows that existing strengthening and slope slope have a significant influence on slope stability and can be used as indicators in evaluating the risk of slope collapse.